Stigmatisasi dalam Novel Izana karya Daruma Matsuura - Muhammad Ihsan Afandi; Fithyani Anwar (Universitas Diponegoro, 2025)
This study analyzes the phenomenon of stigma experienced by the main character in Daruma Matsuura’s novel Izana (誘) using Erving Goffman's stigma theory. Goffman categorizes stigma into three types: abominations of the body, blemishes of individual character, and tribal stigma. The research aims to identify the forms of stigma experienced by Izana, her process of internalizing that stigma, and the strategies of stigma management presented in the novel. Employing a qualitative descriptive method and narrative analysis, the data were gathered through document analysis and literature study, focusing on the primary text of the novel and secondary sources such as Goffman's theoretical framework. The findings reveal that Izana is stigmatized as a “cursed child” due to her unattractive appearance (abomination of the body) and her birth in the year of the Fire Horse (tribal stigma), both of which are culturally associated with misfortune. These factors lead to her internalizing a negative self-image and developing feelings of alienation. The study also finds that stigma management is initially performed by Chigusa, who conceals Izana’s identity through passing, and later by Izana herself, who uses covering to downplay her differences. These strategies reflect complex efforts to resist and adapt to societal rejection. The analysis highlights how literature reflects the social construction of stigma and reveals the psychological and relational consequences of exclusion. This study contributes to literary sociology by showing how fictional narratives can critique real-world practices of marginalization and offer insights into the dynamics of social labeling and resistance. <a href=